Attitude towards mental help-seeking, motivation, and economic resources in connection with positive, negative, and general psychopathological symptoms of schizophrenia: a pilot study of a psychoeducation program - Abbas, Qasir; Baig, Khawar Bilal; Sadiq, Urooj; Habib, Hina Ayaz; Aljhani, Sumayah; Ramzan, Zoobia (Frontiers in Psychiatry, 2024)
Introduction Schizophrenia is typically treated with medication as the first approach, but additional strategies are necessary to enhance the effectiveness of this treatment for better outcomes. However, it is crucial to explore methods, alongside medication, that promote a positive attitude towards seeking mental health support and alleviate symptom severity among non-institutionalized individuals of different age groups in Pakistan. Thus, this pilot study aimed to utilize a psychoeducation program to enhance patients’ motivation and attitudes toward seeking treatment, decrease symptom severity, and investigate the role of financial factors in their illness journey. Methods In this preliminary investigation, our focus was on individuals who had been diagnosed with schizophrenia and were receiving treatment from various hospitals and primary care clinics. Following a thorough screening process, 255 participants met the eligibility criteria, and 220 completed the psychoeducation program. The study included both male and female participants, with 143 (56.08%) being men and 112 (43.82%) being women. Regarding marital status, 123 (48.24%) were single, 98 (38.43%) were married, and 34 (13.33%) were divorced widowers or widows. The age range of the respondents varied from 18 to 52 years, with a mean age of 35.45 and a standard deviation of 10.27. Results The results indicated a decrease in symptom severity following a 16-week psychoeducation program. The psychoeducation program significantly reduced the positive symptoms, negative symptoms, and general psychopathological symptoms among patients. Similarly, significant improvement was observed in patients’ motivation toward treatment and they actively participated in treatment after getting psychoeducation about the treatment. Similarly, after the psychoeducation program significant improvement was seen in patients’ attitudes towards help-seeking and perceived mental health functioning. Conclusion In summary, the findings suggest that our psychoeducation program has the potential to positively impact the motivation and help-seeking attitudes of schizophrenia patients towards treatment. Moreover, there is a need for further exploration of psychoeducation programs for schizophrenia, particularly in countries facing economic challenges. This study paves the way for the development of an indigenous psychoeducation program tailored to Pakistani schizophrenia patients, with potential applicability for Urdu-speaking individuals. Clinical Trial Registration https://www.thaiclinicaltrials.org/show/TCTR20210208003, identifier TCTR20210208003.